Dynamics of resilience in forced migration: a 1-year follow-up study of longitudinal associations with mental health in a conflict-affected, ethnic Muslim population. Issue 2 (16th February 2015) - Siriwardhana, Chesmal; Abas, Melanie; Siribaddana, Sisira; Sumathipala, Athula; Stewart, Robert
Abstract : Objective: The concept of 'resilience' is of increasing interest in studies of mental health in populations facing adversity. However, lack of longitudinal data on the dynamics of resilience and non-usage of resilience-specific measurements have prevented a better understanding of resilience-mental health interactions. Hence, the present study was conducted to investigate the stability of levels of resilience and its associations with sociodemographic and mental health exposures in a conflict-affected internal-migrant population in Sri Lanka. Design: A prospective follow-up study of 1 year. Setting: Puttalam district of North Western province in postconflict Sri Lanka (baseline in 2011, follow-up in 2012). Participants: An ethnic Muslim population internally displaced 20 years ago (in 1990) from Northern Sri Lanka, aged 18 or above and currently in the process of return migration. Measures: It was hypothesised that levels of resilience would be associated with mental health outcomes. Resilience was measured on both occasions using the 14-item Resilience Scale (RS-14), social support by the Multidimensional Social Support Scale and Lubben Social Network Scale and common mental disorders by the Patient Health Questionnaire (PHQ). Results: Of 450 participants interviewed at baseline in 2011, 338 (75.1%) were re-interviewed in 2012 after a 1-year follow-up. The mean resilience scores measured by RS-14 were 80.2 (95% CI 78.6 to 81.9) at baseline and 84.9 (83.5 to 86.3) at follow-up. At both time points, lower resilience was independently associated with food insecurity, lower social support availability and social isolation. At both time points, there were significant associations with common mental disorders (CMDs) in unadjusted analyses, but they only showed independence at baseline. The CMD prevalence, maintenance and incidence at follow-up was 8.3%, 28.2% and 2.2%, respectively. Conclusions: In this displaced population facing a potential reduction in adversity, resilience was more strongly and robustly associated with economic and social factors than with the presence of mental disorder.